PENERAPAN MEDIA GAMBAR PUZZLE DALAM PEMBELAJARAN IPS KELAS V DI SD NEGERI 1 SURULANGUN - Kukuh Prasetyo; Yeni Asmara; Andri Valen (LP4MK STKIP PGRI Lubuklinggau, 2023)
his study aims to determine the completeness of the social studies learning outcomes of class V students at SD Negeri 1 Surulangun after the application of the puzzle image media. The media used in this research is the puzzle image media. The population is all students of class V Surulangun, amounting to 43 students, while the sample is a class that is one of the non-random sampling techniques where the writer determines the sampling by determining special characteristics. Data collection was done by using test techniques. The data were analyzed by using the normality test and statistical t-test. The results showed that the students 'pret-test mean score was 34.62 and the students' post-test mean score was 74.74. Based on the t-test analysis at a significant level = 0.05. Obtained ttable = 1.73 and tcount (7.26), so it can be concluded that the application of puzzle image media in the fifth grade social studies learning at SD Negeri 1 Surulangun is significantly complete. Keywords: Application of puzzle image media, SD IPS learning